International society of blood transfusion working party on red cell immunogenetics and terminology: report of the Seoul and London meetings. (27th June 2016) - Storry, J. R.; Castilho, L.; Chen, Q.; Daniels, G.; Denomme, G.; Flegel, W. A.; Gassner, C.; de Haas, M.; Hyland, C.; Keller, M.; Lomas‐Francis, C.; Moulds, J. M.; et al.
Abstract : The Working Party has met twice since the last report: in Seoul, South Korea 2014, and in London, UK 2015, both in association with the International Society of Blood Transfusion (ISBT) Congress. As in previous meetings, matters pertaining to blood group antigen nomenclature were discussed. Eleven new blood group antigens were added to seven blood group systems. This brings the current total of blood group antigens recognized by the ISBT to 346, of which 308 are clustered within 36 blood groups systems. The remaining 38 antigens are currently unassigned to a known blood group system.